KONSEP DIRI REMAJA DUSUN ARGASARI DESA KOWANGAN KOTA TEMANGGUNG DITINJAU DARI PRESTASI BELAJAR - Farah Dina Insani (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2020)
This study explores adolescent self-concept in terms of learning achievement. The purpose of writing this article is to know more about the self-concept of adolescents in terms of their learning achievement.In this study, the authors used data collection methods with observation, interview, and documentation methods, as in data collection techniques in qualitative research. The object of study in this article focuses on adolescent self-concept in terms of learning achievement. learning achievement is one proof that a teenager has a positive self-concept or vice versa.The Argasari neighborhood is located in the Kowangan Village, Temanggung District, Temanggung Regency (Located in the center of Temanggung City), Central Java. Argasari neighborhood consists of 53 family heads from various backgrounds. There are those who work as farmers, laborers and civil servants. However, it was found that there were differences in the identity of adolescents between those with harmonious families and broken home families. Many teenagers in the Argasari neighborhood of Kowangan Village, Temanggung City, are currently formed because of an unsupportive environment. Many of the teenagers in the Argasari neighborhood drop out of school because they don't have the money to continue their schooling. What is surprising is that they admit that they are not strong enough to pay for their schools, but there is always money to buy cigarettes and rolling tobacco. However, there are some children who are from underprivileged families and they don't smoke, but they struggle and work hard to continue their studies without relying on fees from their parents and trying to get scholarships.